Jazz improvisation as situated cognition: historical and analytical perspectives on the music of Milt Jackson - Gagatsis, Alexander Christos (2018)
This thesis examines the life and music of vibraphonist Milt Jackson as a form of situated cognition. Situated cognition theory, or situated learning, argues for the ecological specificity of perception: namely that knowledge is situated in activity bound to social, cultural and physical contexts. My study brings such a perspective to mid-twentieth-century jazz practice with the view of bringing to the fore a certain cultural knowledge with regards to the practice and expression of jazz in the 1940s and 1950s, and to highlight important parts of its knowledge base as these are evident in the musical outputs of Jackson. In so doing, this thesis also attempts to offer the first substantial historical account of Jackson’s upbringing in Detroit, based on detailed archival research, and highlight some of the influential environments to which he was exposed. Typical of his generation, Jackson forged diverse musical influences into a personal sonic signature; in this development, the Detroit communities were highly instrumental.